Interleukin 4 Affects Epilepsy by Regulating Glial Cells: Potential and Possible Mechanism - Chen, Lu; Zhu, Lin; Lu, Di; Wu, Zhe; Han, Yanbing; Xu, Puying; Chang, Lvhua; Wu, Qian (Frontiers in Molecular Neuroscience, 2020)
Epilepsy is a chronic brain dysfunction induced by abnormal neuronal discharge that is caused by complicated psychopathologies. Recently, accumulating studies have revealed a close relationship between inflammation and epilepsy. Specifically, microglia and astrocytes are important inflammatory cells in the central nervous system that have been proven to be related to the pathogenesis and development of epilepsy. Additionally, interleukin 4 (IL-4) is an anti-inflammatory factor that can regulate microglia and astrocytes in many aspects. This review focuses on the regulatory role of IL-4 in the pathological changes of glial cells related to epilepsy. We additionally propose that IL-4 may play a protective role in epileptogenesis and suggest that IL-4 may be a novel therapeutic target for the treatment of epilepsy.